COVID-19 mitigates the response to TKIs in patients with CML via the inhibition of T-cell immunity - He, Na; Li, Guosheng; Liu, Jinting; Liu, Wancheng; Tian, Ruifeng; Ma, Daoxin (Frontiers in Immunology, 2024)
IntroductionChronic myeloid leukemia (CML) is a severe hematological malignancy characterized by BCR-ABL fusion gene. The advent of tyrosine kinase inhibitors (TKIs) targeting BCR-ABL has improved the landscape of CML treatment dramatically. The occurrence of coronavirus disease 2019 (COVID-19) has challenged many cancers. However, its effect on TKI therapy of CML remains unknown.MethodsIn this study, we collected peripheral blood from chronic phase CML patients treated with TKIs at low-level BCR-ABL P210 during COVID-19 pandemic, and determined the alterations of BCR-ABL P210 by applying the well-established BCR-ABL P210 detection system.ResultsOur results showed that the level of BCR-ABL P210 of CML patients was significantly elevated shortly after contracting COVID-19, and then recovered to pre-infection level within one month. The elevated degree of P210 was positively correlated with the duration of COVID-19. And the level of P210 was elevated in CML patients that took COVID-19 vaccination. Furthermore, lymphocyte subsets and cytokine detections were performed by flow cytometry to analyze the alteration of immune responses. Our results showed that effector CD8+ T (Teff) cells were significantly downregulated while naïve CD8+ T cells or Treg cells were obviously upregulated in P210-elevated CML patients after contracting COVID-19 compared to that in P210-unchanged or decreased CML patients. Moreover, the SARS-CoV-2 pseudovirus was constructed to further determine its effects. The results showed that the level of BCR-ABL P210 was upregulated upon transfection of SARS-CoV-2 pseudovirus into blood samples of CML patients.DiscussionOur results demonstrate that COVID-19 suppresses the immune activity and consequentially elevates the level of BCR-ABL P210 of CML patients.